Family violence and runaway children in prisoner populations of Latin America - Agoff, Carolina (International journal of comparative and applied criminal justice, 2024)
The paper aims to analyse the links between domestic violence and children abandoning their family home, using new empirical evidence from the Latin American inmate population. Interest in this group is obvious, as it is precisely because they ran away from home that many may have ended up in a criminal environment and finally, in prison. Among prison inmates, family violence is a strong predictor of abandoning the childhood home. Such inmates have a significantly higher risk of reporting having run away from home at least once before the age of 15, irrespective of their family, peer/school, and neighbourhood context. Domestic violence is a risk factor, triggering a series of events that result in children running away from their homes (victims of domestic violence or witnesses to it). This study suggests a relationship between different configurations of domestic violence and runaways, and provides an additional benefit by relating these two elements to the inmate population.